Genome-wide analysis of RNAs associated with Populus euphratica Oliv. heterophyll morphogenesis. Issue 1 (December 2018) - Qin, Shao-Wei; Jiang, Ren-Jun; Zhang, Na; Liu, Zhan-Wen; Li, Cai-Lin; Guo, Zhong-Zhong; Bao, Liang-Hong; Zhao, Li-Feng
Abstract The desert plantPopulus euphratica Oliv. has typical heterophylly; linear (Li), lanceolate (La), ovate (Ov) and broad-ovate (Bo) leaves grow in turn as trees develop to maturity.P .euphratica is therefore a potential model organism for leaf development. To investigate the roles of RNAs (including mRNAs, miRNAs, lncRNAs and circRNAs) in the morphogenesis ofP .euphratica heterophylls, juvenile heterophylls were sampled individually, and then, the expression patterns of miRNAs, mRNAs, lncRNAs and circRNAs were analysed by small RNA sequencing and strand-specific RNA sequencing. We found that 1374 mRNAs, 19 miRNAs, 71 lncRNAs and 2 circRNAs wereP .euphratica heterophyll morphogenesis–associated (PHMA) RNAs; among them, 17 PHMA miRNAs could alter the expression of 46 PHMA mRNAs. Furthermore, 11 lncRNAs and 2 circRNAs interacted with 27 PHMA mRNAs according to the ceRNA hypothesis. According to GO and KEGG pathway analysis, PHMA RNAs were mainly involved in metabolism, response to stimulus and developmental processes. Our results indicated that external environmental factors and genetic factors inP .euphratica co-regulated the expression of PHMA RNAs, repressed cell division, reinforced cell growth, and ultimately resulted in the morphogenesis ofP .euphratica heterophylls.